Perempuan Sebagai “Orang Tua” Tunggal - Wenno, Margery Malinda (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2022)
A single parent, as the literal meaning suggests, is someone who cares for, supports, and raises their child without a partner. Women who give birth outside of marriage have become a cross-border phenomenon, occurring both within church communities and among people of various beliefs and backgrounds. Women who become single parents require support in facing various challenges. As single parents, women experience a range of issues from psychological, socio-cultural, and economic aspects.